Coping with Financial Crises Some Lessons from Economic History (Studies in Economic History,, 2018)
This edited volume is based on original essays first presented at the World Economic History Conference, Kyoto, Japan, in August 2015. It also includes three essays subsequently written especially for this volume. All of the essays focus on financial markets in the periods leading up to, during, and after financial crises, and all are based on new data and archival research. The essays in this volume enlarge the range of historical evidence on the causes and potential cures for financial crises. While not neglecting the United States or Britain, the usual focus of financial historians, it includes studies of financial markets in times of crisis in Japan, Sweden, France, and other countries to achieve a truly global and historical perspective. As a result of the research reported here the reader will be made aware of several neglected factors that have shaped financial crises including the most recent crisis. These factors are (1) the role played by monetary policy in causing and ameliorating crises, (2) the role played by international contagion in private financial markets in propagating financial crises, (3) the role played by variations in the institutional structures of financial markets in determining the impact of financial crises, and (4) the role played by the social background of the central bankers who must contend with financial crises in determining the final outcome.